The Problems in Mineral and Coal Mining Regulations Perspectives Political Law and Responsive Law - Putra Astomo (Universitas Syiah Kuala, 2021)
Minerals and coal are two elements of natural wealth owned by the Indonesian people and managed according to the country's economic system as regulated in Article 33 of the 1945 Constitution of the Republic of Indonesia. This paper examines the criticism of the birth of mineral and coal mining legal products amid the Corona Virus Pandemic Disease (Covid-19) that is deadly and afflicts most countries in the world including Indonesia, namely Law Number 3 of 2020 on Amendments to Law Number 4 of 2009 on Mineral and Coal Mining thus the regulations of mineral and coal mining creates problems. The approach method was used a socio legal approach. The results of the study show that problems that arise in the regulations of mineral and coal mining in terms from the political law and responsive law perspectives due to two factors between: (1) Contrary with establishment of legislation principles related discussion the draft Law on Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining. (2) Contrary with responsive law because participations of community low in establishment the draft Law on Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining.